EFL Teachers’ Pedagogical Content Knowledge (PCK) and Teaching Practice: Metekel Zone Junior Schools in Focus, Ethiopia - Hirpa, Tadesse; Simegn, Birhnu; Amogne, Dawit; Getnet, Meseret (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2023)
In this explanatory sequential mixed method study, the researcher attempted to investigate the EFL teachers’ status of CK, PK, PCK, classroom practice and the relationships among these variables. Comprehensive and purposive sampling techniques were used. Quantitative and qualitative data analyses methods were employed in the study. The least knowledge the teachers owned was CK whereas classroom practice was found to be relatively the highest. They had moderate PK in assessing students’ understanding of topics, in drawing up clear classroom rules, creating a friendly atmosphere, and developing a good relationship with students. However, the overall finding revealed that the teachers were not well equipped with PK. They had moderate PCK in designing instructional objectives and context, and in using appropriate examples to explain concepts related to the subject matter whereas their knowledge of students’ understandings and misunderstandings was inadequate. They had low knowledge to diagnose the notions that were problematic for students and to think why these concepts became difficult. There was a strong positive correlation between CK and classroom practice. The correlation between CK and PK was fair whereas there was a weak positive correlation between PK and classroom practice. There was not statistically significant relationship between PCK and classroom practice.